Atlas of Cronkhite-Canada Syndrome - Hokari, Ryota; Hisamatsu, Tadakazu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This manual treats both conceptual and practical aspects of the gastrointestinal polyposis syndrome characterized by dermatologic manifestations. The book offers both detailed and comprehensive analysis of the endoscopic findings achieved from 88 cases, which led to novel concepts and classification of the dermatologic manifestations according to distribution pattern, the thickness of mucosa, and intervening inflamed mucosa between polyps. The book also offers comparisons of the endoscopic features to pathological features. Abundant illustrations show the observations of the malignant lesions using special lights, such as NBI and BLI, to provide a thorough view of the Cronkhite-Canada syndrome (CCS) polyp. Atlas of Cronkhite-Canada Syndrome simplifies a complicated picture of the rare disease. It is essential guidance for gastroenterologists and pathologists who pursue the new diagnostic approach and treatment for CCS. It also attracts clinicians who are interested in the latest updates on this field and those who encountered the CCS patients with refractory to corticosteroid treatment. Owing to difficulties in detecting premalignant adenomas in the face of multiple inflammatory pseudopolyps, the risk of colon cancer in CCS patients may be elevated. Additionally, it is important to have a broader understanding of the disease and understanding of the treatment strategy, as endoscopy for GI disease becomes widespread in developing countries, and the number of patients will likely increase.
1 Cronkhite-Canada Syndrome Disease -- 2 Endoscopic Images Per Organ -- 3 Endoscopic Images of Small Bowel Capsule Endoscopy, Balloon-Assisted Enteroscopy and Image-Enhanced Endoscopy -- 4 Endoscopic Images of Coincident Carcinoma and Adenoma to Differentiate from Non-Neoplastic Polyps -- 5 Comparison of Pathological and Endoscopic Images (per Organ) -- 6 Case-Based Images: First Attack Case -- 7 Case-based images: Relapse - Remitting Cases/Chronic Continuous Cases -- 8 Case-based images: Steroid-Resistant/Refractory/Intolerant Cases -- 9 Case-based images: Cases Treated with Other Than Corticosteroids -- 10 Case-Based Images: Cases with Atypical Clinical Symptoms/Possible Cases -- 11 Case-based images: Cases with Coincident Esophageal Lesions/Coincident.
Keywords: Gastroenterology; Endoscopy; Oncology; Pathology; Gastroenterology; Endoscopy; Oncology; Pathology; Intestinal Polyposis; Intestinal Polyps